Penggunaan Media Roda Pintar Untuk Meningkatkan Kemampuan Menulis Anak Usia 4-5 Tahun Di Sukawargi - Jubaedah, Endah; Asiah, Euis; Maosul, Asep (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2025)
This research is motivated by observational data that shows the low achievement of writing skills in early childhood at Al Waladul Huda Kindergarten with the discovery of several problems including; writing skills in group A are still lacking, children have not been able to make a meaningful scribble, children have not been able to write letters from A-Z. The purpose of this study is to describe the use of Smart Wheel media to improve writing skills in children aged 4-5 years. The subjects in this study were 10 respondents with 6 male subjects and 4 female subjects. The type of research used in this study is qualitative research with a classroom action research design or PTK. The results of this study indicate that the use of Smart Wheel media to improve writing skills in children aged 4-5 years shows a significant increase, can be seen from the percentage of success, from the results of initial observations there are 0% of children developing very well, 0% of children developing according to expectations, 40% of children starting to develop and 60% of children have not developed. After implementing the use of Smart Wheel media to improve writing skills in children aged 4-5 years, the final results of cycle I reached a 60% increase in writing skills in children aged 4-5 years, and the final results of cycle II reached 100%. Keywords: Early Childhood, Smart Wheel Media, Writing